La figure du père sacrificateur de sa fille dans les rituels athéniens - Claudine Leduc (Pallas, 2011)
In classical era’s Athens several rituals have for founding myth the sacrifice of a daughter pro tou gamou offered by her father. At Brauron and Munichie the immolation of civic heroines and the symbolic sacrifice of young girls in honour of Artemis provide a continuity in the analysis and show the extent to which the patria potestas and the coercive power of an Athenian father over his daughter bear on both her person and her future.